I Think I Am a Behaviorist; Therefore I Am - Catania, A. Charles (Taylor & Francis, 2015)
John Staddon is Professor of Psychology at Duke University and was co-editor, with Werner K. Honig, of the Handbook of Operant Behavior (Prentice-Hall, 1977). A. Charles Catania is Professor of Psychology at the University of Maryland Baltimore County and the author of Learning (4th ed., Prentice-Hall, 1998).